2006
DOI: 10.1111/j.0021-9029.2006.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Factors, Money Attitudes, Financial Knowledge, and Credit‐Card Debt in College Students1

Abstract: The issue of credit-card debt among college students has received increasing attention. This study explored factors hypothesized to be causes and effects of credit-card debt in 448 students on five college campuses. Students reported an average of $1,035 (SD 5 $1,849) in debt, including students without credit cards or credit-card debt. Lack of financial knowledge, age, number of credit cards, delay of gratification, and attitudes toward credit-card use were related to debt. Sensation seeking, materialism, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
297
3
25

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(358 citation statements)
references
References 33 publications
(53 reference statements)
16
297
3
25
Order By: Relevance
“…Assessment of research findings have revealed that young adults, especially college students fail to manage their expenditure and therefore fall into financial strain. Previous studies related to students' financial management have shown that upon entering university, students have more access to credit cards and therefore experience high level of stress due to high debt, and most have financial problems and perceive low level of satisfaction with their financial situation (Holub, 2002;NellieMae, 2002;Norvilitis et al, 2006;Norvilitis, Szablicki, & Wilson, 2003). However, these problems may be rooted in a low level of financial knowledge and the high effect of friends and media on students' financial behaviour and negative attitude toward money (Norvilitis & Santa Maria, 2002;Roberts & Jones, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of research findings have revealed that young adults, especially college students fail to manage their expenditure and therefore fall into financial strain. Previous studies related to students' financial management have shown that upon entering university, students have more access to credit cards and therefore experience high level of stress due to high debt, and most have financial problems and perceive low level of satisfaction with their financial situation (Holub, 2002;NellieMae, 2002;Norvilitis et al, 2006;Norvilitis, Szablicki, & Wilson, 2003). However, these problems may be rooted in a low level of financial knowledge and the high effect of friends and media on students' financial behaviour and negative attitude toward money (Norvilitis & Santa Maria, 2002;Roberts & Jones, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen and Volpe (1998) conducted a study of financial practices among college students and their findings indicate that financial knowledge has positive and significant effect on students' financial management. Researchers in the field of financial education (Hilgert & Hogarth, 2003;Norvilitis et al, 2006;Perry & Morris, 2005) reviewed previous findings and concluded that financial literacy is one of the most important determinants of financial management among college students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study focusing on psychological variables, Norvilitis, Merwin, Osberg, Roehling, and Kamas (2006) investigated the factors affecting credit-card debt in 448 students from five US universities. Older students, students with more credit cards and those who are less knowledgeable about financial issues reported a higher amount of credit card debt.…”
Section: Introductionmentioning
confidence: 99%
“…Better educated individuals will be more resourceful, in searching for, and using quality information, which may be positively related to higher quality investment decision-making [30,31]. Similarly, education is positively related to socio-economic development [32] and it has been considered a crucial component of cultural capital [7,12].…”
Section: Acculturation As Language and Social Practicesmentioning
confidence: 99%